GROUNDWATER QUALITY ASSESSMENT FOR IRRIGATION PURPOSES AT THE WESTERN PORTION OF THE RIVER NILE– MINIA DISTRICT- EGYPT - Morsi, Mamdouh Salama (International Journal of Research -GRANTHAALAYAH, 2018)
The main goal of this research is assessment the groundwater resources for irrigation purposes at the western portion of the River Nile –Minia district- Egypt. The research depend on representation and calculation the resulted of chemical analysis of 96 groundwater samples collected from 96 pumping well During autumns 2011 from quaternary aquifer. the resulted reviled that; 25% of groundwater samples within the range of none restriction on use and the rest are margin according TDS content, most of samples are good for irrigation in all soils as they located in classes (C2-S1) and (C3-S1) and suitable for irrigation all crops as belong to SAR values and RSC hazard. But it restricted by boron ion concentration.